Effects of welding speed on the multiscale residual stresses in friction stir welded metal matrix composites. Issue 5 (May 2019) - Zhang, X.X.; Wu, L.H.; Andrä, H.; Gan, W.M.; Hofmann, M.; Wang, D.; Ni, D.R.; Xiao, B.L.; Ma, Z.Y.
Abstract: The effects of welding speed on the macroscopic and microscopic residual stresses (RSes) in friction stir welded 17 vol.% SiCp/2009Al-T4 composite plates were studied via neutron diffraction and an improved decoupled hierarchical multiscale modeling methods. Measurements showed that the macroscopic and total RSes had the largest variations in the longitudinal direction (LD). Increasing the welding speed led to higher values of measured LD macroscopic and total RSes in the matrix. The welding speed also significantly influenced the distributions and magnitudes of the microscopic RSes. The RSes were predicted via an improved hierarchical multiscale model, which includes a constant coefficient of friction based thermal model. The RSes in the composite plates before friction stir welding (FSW) were computed and then set as the initial states of the FSW process during modeling. This improved decoupled multiscale model provided improved predictions of the temperature and RSes compared with our previous model.